The Role of Mindfulness in Addressing Burnout among Healthcare Professionals: A Systematic Review - Indah Sari Liza Lubis (CV. Creative Tugu Pena, 2024)
Those employed in the field of health are a profession that interacts directly with patients on a regular basis and therefore are exposed to significant stressors. The considerable number of responsibilities, the high complexity of the work, and the demands placed upon health workers make the health worker profession susceptible to stress and burnout. The objective of this study is to ascertain the impact of mindfulness-based interventions on mitigating burnout among healthcare professionals at Hospital